High-precision resistor device

CN122889532APending Publication Date: 2026-10-09HUNAN SHENGZEYUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611215625.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

一方面,环氧树脂本体的吸水率较高,水汽及外部腐蚀性离子仍可经缓慢渗透通过该层;另一方面,环氧树脂与内部硅酮缓冲层的热膨胀系数存在较大差异,在长期温度循环作用下,封装层内部容易产生微裂纹

Benefits of technology

本发明中第一阻隔层为由至少两种不同金属氧化物纳米层交替堆叠构成的无机纳米叠层,在垂直方向上引入大量异质界面。当水分子或腐蚀性离子沿膜厚方向扩散时,每遇到一个异质界面,即因两侧材料的晶格常数、化学组成和微观结构差异而发生散射、反射或路径偏折。这种“曲折路径效应”将原本可能垂直贯穿的短直通道转化为需要绕行的漫长曲折路径,极大延长了渗透物质到达底层电阻合金膜层所需的时间。同时,不同氧化物层在沉积过程中,其成核和生长模式有所差异,后续沉积的纳米层可有效覆盖前一层中可能存在的微观缺陷,层与层之间相互“封堵”,使贯穿性缺陷的概率呈指数级下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889532A_ABST
    Figure CN122889532A_ABST
Patent Text Reader

Abstract

The application relates to the field of resistor devices, in particular to a high-precision resistor device which comprises a resistor body, the resistor body is composed of a ceramic substrate, a resistor alloy film layer formed on the ceramic substrate, a silicone resin layer covering the resistor alloy film layer, a first barrier layer covering the silicone resin layer and a second barrier layer; the first barrier layer is an inorganic nano-laminate which is composed of at least two nano-layers of different metal oxides which are alternately stacked; the second barrier layer is a vapor deposition polymer layer formed on the first barrier layer; the application can greatly improve the service life of the high-precision resistor in a double-85 aging test, and the resistance change rate is kept within 0.5%, the precision degradation and failure problem of the thin-film resistor caused by electrochemical corrosion in harsh environments is solved, and the application has outstanding substantial characteristics and significant progress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-precision resistors, specifically a high-precision resistor. Background Technology

[0002] Chip resistors are generally classified into two categories: thick-film resistors and thin-film resistors. Thick-film resistors are manufactured using processes such as screen printing, drying, sintering, and resistance adjustment. The film thickness is typically greater than 10μm, and they feature a wide resistance range, high reliability, and small size, making them widely used in various electronic products. Thin-film resistors, on the other hand, are formed by depositing materials with specific resistivity onto the surface of a ceramic substrate using methods such as vacuum evaporation and magnetron sputtering. The film thickness can be controlled to 1μm or less. Compared to thick-film resistors, thin-film resistors offer higher resistance accuracy, a lower temperature coefficient, and superior resistance stability, making them suitable for applications with more stringent requirements for accuracy and reliability.

[0003] However, in harsh operating environments with high temperature, high humidity, and electric field coupling, the metal film layer of thin film resistors is prone to electrochemical corrosion, leading to resistance drift or even open circuit failure, which seriously affects the long-term reliability and precision characteristics of the device.

[0004] To address the electrochemical corrosion problem of thin-film resistors, existing technologies have proposed a composite encapsulation solution using silicone resin and epoxy resin. In this solution, silicone resin is directly applied to the resistive film layer and laser-adjusted trenches. Its excellent hydrophobic properties create a hydrophobic layer on the metal film surface, inhibiting the spread and adhesion of liquid water at the source and eliminating the necessary conditions for electrochemical corrosion. An epoxy resin layer is then coated over the silicone resin, acting as a robust physical barrier to prevent the penetration of external moisture and liquid water, and providing protection against mechanical friction, impact, and external chemical corrosion.

[0005] However, the aforementioned composite encapsulation solution still has shortcomings in practical applications. On the one hand, the epoxy resin itself has a high water absorption rate, allowing moisture and external corrosive ions to slowly penetrate through the layer. On the other hand, the thermal expansion coefficients of the epoxy resin and the inner silicone buffer layer differ significantly, making it prone to microcracks under long-term temperature cycling. These microcracks become channels for rapid moisture intrusion, ultimately leading to electrochemical corrosion, resulting in decreased device precision and even functional failure. Therefore, effectively improving the corrosion resistance of the outer barrier is a pressing technical problem that needs to be solved. Summary of the Invention

[0006] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes a high-precision resistor device.

[0007] The technical solution adopted is as follows: A high-precision resistor device includes a resistor body, which is composed of a ceramic substrate; a resistor alloy film layer formed on the ceramic substrate; and a silicone resin layer covering the resistor alloy film layer. It also includes a first barrier layer and a second barrier layer covering the silicone resin layer; the first barrier layer is an inorganic nanolayer stack, which is composed of nanolayers of at least two different metal oxides stacked alternately; the second barrier layer is a vapor-deposited polymer layer formed on the first barrier layer.

[0008] Furthermore, the inorganic nanolayer is composed of alternating stacks of aluminum oxide nanolayers and titanium dioxide nanolayers.

[0009] Furthermore, the total thickness of the inorganic nanolayer is 50-200 nanometers.

[0010] Furthermore, the first barrier layer is fabricated using an atomic layer deposition process.

[0011] Furthermore, the oxygen source used in the atomic layer deposition process is ozone or oxygen plasma.

[0012] Furthermore, the vapor-deposited polymer layer is parylene.

[0013] Furthermore, the thickness of the vapor-deposited polymer layer is 5-25 micrometers.

[0014] Furthermore, the resistance alloy film is a nickel-chromium alloy or tantalum nitride film, and the resistance alloy film has a resistance pattern, which is formed by photolithography and laser trimming.

[0015] Furthermore, the fabrication method of the aforementioned high-precision resistive device includes: The resistor body is placed in an atomic layer deposition reaction chamber, and at least two kinds of metal precursors and oxygen source precursors are alternately introduced to grow a first barrier layer in situ on the silicone resin layer, which is composed of alternating stacks of different metal oxide nanolayers. A resistor body with the first barrier layer is placed in a vapor deposition system, and a polymer layer is deposited on the first barrier layer to form a second barrier layer.

[0016] Furthermore, the silicone resin layer is pre-activated with ozone before forming the first barrier layer. Ozone activation introduces polar functional groups, which chemically adsorb with the atomic layer deposition metal precursor, forming strong chemical bonds and significantly improving the adhesion between the inorganic nanolayer and the organosilicone resin layer.

[0017] This invention proposes a high-precision resistor device, which has the following beneficial effects: In this invention, the first barrier layer is an inorganic nanolayer composed of at least two different metal oxide nanolayers stacked alternately, introducing a large number of heterogeneous interfaces in the vertical direction. When water molecules or corrosive ions diffuse along the film thickness direction, each time they encounter a heterogeneous interface, scattering, reflection, or path deflection occurs due to differences in the lattice constants, chemical compositions, and microstructures of the materials on both sides. This "zigzag path effect" transforms what would otherwise be a short, straight channel that penetrates vertically into a long, tortuous path that requires detours, greatly extending the time required for the penetrating substance to reach the underlying resistance alloy film layer. Simultaneously, different oxide layers exhibit different nucleation and growth patterns during deposition, allowing subsequently deposited nanolayers to effectively cover any microscopic defects that may exist in the previous layer. The layers mutually "block" each other, causing the probability of penetrating defects to decrease exponentially.

[0018] The heterogeneous interface formed between two metal oxides is not only a physical geometric boundary, but also exhibits differences in band structure and chemical potential. The space charge region and band shift present at the interface constitute a potential barrier to the migration of charged ions (such as corrosive ions like chloride and sodium ions), effectively inhibiting the directional migration of ions driven by an applied electric field. Furthermore, the different isoelectric points and surface acidity / basicity of the different metal oxides have varying effects on the adsorption and surface diffusion behavior of water molecules, causing water molecules to tend to reorient or desorb at the interface, further hindering their continuous penetration.

[0019] The first barrier layer is prepared using atomic layer deposition (ALD). This process is based on surface self-limiting chemisorption reactions, growing only a single atomic layer or sub-atom layer film per deposition cycle. Because the precursor gas can diffuse sufficiently to the complex three-dimensional surface structure, this process achieves true conformal coating on the resistor body. The deposition thickness is highly uniform across flat areas, trimmed trench sidewalls, laser-cut edges, and anisotropic steps, eliminating the shadowing effect and poor step coverage problems common in traditional physical vapor deposition (PVD) or chemical vapor deposition (CVD). The sequential stacking of ultrathin layers in ALD fundamentally eliminates the formation of through-holes, resulting in a film density close to the theoretical density. Furthermore, the oxygen source used in ALD is ozone or oxygen plasma, whose strong oxidizing properties ensure sufficient oxidation of the metal precursor and complete removal of ligands, resulting in a high-purity oxide film with few defects and optimal barrier performance.

[0020] Before the first barrier layer is deposited at atomic layers, the silicone resin layer is ozone-activated to introduce polar oxygen-containing functional groups onto the silicone resin surface. When the metal precursor pulse enters the reaction chamber, these active polar groups can undergo chemical adsorption or ligand exchange reactions with the precursor molecules to form strong chemical bonds. This in-situ generated chemical bond interface has a significantly improved bonding strength compared to physical adhesion relying solely on van der Waals forces or mechanical locking. It can effectively resist interfacial shear stress caused by the difference in thermal expansion coefficients of organic / inorganic materials during temperature cycling and damp heat aging, preventing delamination, peeling, and the formation of interfacial gaps, thus ensuring the integrity of the protective structure throughout its service life.

[0021] The second barrier layer is a vapor-deposited polymer layer formed on top of the first barrier layer, preferably parylene, prepared using the Gorham vapor deposition polymerization method. Parylene itself has extremely low water absorption; its molecular chain consists of alternating benzene rings and methylene groups, containing no hydrophilic polar groups, resulting in extremely low solubility and diffusion coefficients for water molecules. Liquid water droplets have a large contact angle on the parylene surface, exhibiting a hydrophobic state and making them difficult to spread and adhere to. This layer, acting as the first line of defense, effectively blocks most external liquid and gaseous water molecules from penetrating inward, significantly reducing the water vapor concentration gradient reaching the surface of the first barrier layer and alleviating the barrier burden on the inorganic nanolayers.

[0022] While inorganic nanolayers are dense and possess excellent barrier properties, their fundamental nature as ceramic films results in low fracture toughness. Under external mechanical impact or bending, they are prone to microcracks that propagate along the film thickness. Parylene, as a polymer, exhibits excellent flexibility and ductility, allowing it to undergo elastic or plastic deformation under external mechanical stress, absorbing and dissipating stress energy and preventing stress concentration from being transferred to the internal brittle inorganic layer. Parylene also possesses excellent chemical inertness, being insoluble in most organic solvents at room temperature and resistant to acids, alkalis, and salt spray, providing excellent barrier properties against various corrosive chemicals present in the environment. This layer effectively isolates the relatively fragile inorganic nanolayers, which may contain microscopic surface defects, from the complex external chemical environment, preventing slow chemical reactions or corrosion from corrosive chemicals and inorganic oxides.

[0023] The first barrier layer provides a "rigid" atomic-level barrier, with its tortuous path and interfacial barrier dominating the water vapor barrier function; the second barrier layer provides a "flexible" macroscopic barrier and mechanical protection, with its hydrophobic isolation and stress buffering dominating the physical protection function. Both layers form a gradient transition from inorganic density to organic flexibility in the thickness direction, ensuring both the overall barrier effectiveness of the protective structure and its reliable toughness in the face of mechanical and environmental stresses. This allows for the synergistic utilization of the dual advantages of nano-interfacial barrier and polymer hydrophobic buffering. Compared to traditional single-layer silicone resin, silicone / epoxy composite encapsulation, single inorganic thin film, or single polymer layer, this invention significantly extends the service life of high-precision resistors in the "double 85" aging test, while maintaining the resistance change rate within 0.5%. It solves the problem of precision degradation and failure caused by electrochemical corrosion of thin-film resistors under harsh environments, demonstrating outstanding substantive features and significant progress. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the high-precision resistive device fabricated in the embodiment. The numbers in the diagram represent: 1-Alumina ceramic substrate, 2-Resistance alloy film, 3-Silicone resin layer, 4-First barrier layer, 5-Second barrier layer. Detailed Implementation

[0025] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0026] Example 1: A method for fabricating a high-precision resistive device: An alumina ceramic substrate 1 with a purity of 99.9%, a thickness of 0.4 mm, and a surface roughness Ra < 0.1 μm was selected. After ultrasonic cleaning with acetone, rinsing with deionized water, and drying with nitrogen, the alumina ceramic substrate 1 was placed in the sputtering chamber of a magnetron sputtering equipment. After evacuation, high-purity argon gas was introduced to a working pressure of 0.5 Pa. A resistance alloy film 2 was deposited using a nickel-chromium alloy target (Ni:Cr = 80:20, purity 99.99%) at a DC sputtering power of 300 W. The film thickness was controlled to approximately 100 nm by controlling the deposition time.

[0027] The substrate with the deposited resistive alloy film layer 2 is subjected to photolithography. Positive photoresist is spin-coated, followed by pre-baking, mask alignment exposure, development, and post-baking to form a resistive pattern mask. Argon ion beam etching is used to remove areas not protected by the photoresist, exposing the ceramic substrate while retaining the desired resistive pattern strips. After photoresist removal, the initial resistive pattern is obtained. The substrate then enters a laser trimming station, where a laser trimming machine, under the closed-loop control of a real-time resistance measurement system, performs laser cutting and fine-tuning of the resistive pattern, forming a precise serpentine resistive pattern and trimming grooves. Immediately after trimming, silicone resin is coated onto the resistive alloy film layer 2. A two-component silicone resin (SYLGARD™ 184) is applied to the functional resistive areas using precision dispensing. The coating is cured in a 100°C vacuum oven for 35 minutes to form a silicone resin layer 3 with a thickness of approximately 20 μm, resulting in the resistor body.

[0028] The resistive substrate containing the silicone resin layer 3 was placed in an atomic layer deposition (ALD) reaction chamber. The reaction chamber was equipped with a rapid pulse valve and a precursor heating and delivery system. The metal precursors used were trimethylaluminum (TMA, used for depositing alumina) and titanium tetrachloride (TiCl4, used for depositing titanium dioxide). Ozone was used as the oxygen source precursor, generated from high-purity oxygen via an ozone generator. The reaction chamber temperature was controlled at 180°C, and the carrier gas was high-purity nitrogen (99.9999%) at a flow rate of 20 sccm. Before deposition began, ozone activation and nitrogen purging cycles were pre-performed. Each activation cycle consisted of a 0.5-second ozone pulse followed by a 5-second nitrogen purging, for a total of 50 consecutive cycles. After the activation step, the first barrier layer 4 was deposited, and the deposition process was as follows: A standard alumina cycle consists of: a 0.1-second TMA pulse, a 5-second nitrogen purging, a 0.5-second ozone pulse, and a 5-second nitrogen purging. At this temperature and parameters, the alumina growth rate is approximately 1.1 Å / cycle. A standard titanium dioxide cycle consists of: a 0.3-second TiCl4 pulse, a 6-second nitrogen purging, a 0.8-second ozone pulse, and a 6-second nitrogen purging. The titanium dioxide growth rate is approximately 0.6 Å / cycle.

[0029] The inorganic nanolayers are constructed by alternately executing the above cyclic sequence. In this embodiment, the inorganic nanolayer of the first barrier layer 4 is composed of alternating stacks of aluminum oxide nanolayers and titanium dioxide nanolayers. First, an aluminum oxide nanolayer of about 5 nm is deposited, followed by a titanium dioxide nanolayer of about 5 nm. This process is repeated 10 times. The final inorganic nanolayer has a total thickness of approximately 100 nm.

[0030] The resistive substrate with the first barrier layer 4 grown on it was removed from the ALD reaction chamber and placed on a rotating sample holder in the deposition chamber of the vacuum vapor deposition polymer system. This system uses the classic Gorham chemical vapor deposition method to deposit parylene. A sufficient amount of parylene dimer was weighed and placed in a sublimator, heated to approximately 180°C to sublimate it. The sublimated dimer vapor was carried into a pyrolysis furnace, where it was pyrolyzed at approximately 700°C into reactive parylene diradical monomers. These monomer gases adsorbed, migrated, and polymerized on the surface of the first barrier layer in the deposition chamber to form a high-molecular-weight parylene film. By controlling the deposition time, a second barrier layer 5 with a thickness of 15 micrometers was formed on the first barrier layer.

[0031] Example 2: This example is essentially the same as Example 1, except that the inorganic nanolayer of the first barrier layer 4 is formed by alternating stacks of aluminum oxide nanolayers and titanium dioxide nanolayers. First, an aluminum oxide nanolayer of approximately 5 nm is deposited, followed by a titanium dioxide nanolayer of approximately 5 nm. This process is repeated five times. The final total thickness of the inorganic nanolayer is approximately 50 nm.

[0032] Example 3: This example is essentially the same as Example 1, except that the inorganic nanolayer of the first barrier layer 4 in this example is composed of alternating layers of aluminum oxide nanolayers and titanium dioxide nanolayers. First, an aluminum oxide nanolayer of approximately 5 nm is deposited, followed by a titanium dioxide nanolayer of approximately 5 nm. This process is repeated 20 times. The final total thickness of the inorganic nanolayer is approximately 200 nm.

[0033] Example 4: Basically the same as Example 1, except that the second barrier layer 5 is still made of parylene and the thickness of the second barrier layer is 5 micrometers.

[0034] Example 5: It is basically the same as Example 1, except that the second barrier layer 5 is still made of parylene and the thickness of the second barrier layer is 25 micrometers.

[0035] Comparative Example 1: The process is basically the same as in Example 1, except that the preparation steps of the first barrier layer 4 and the second barrier layer 5 are omitted. That is, after the silicone resin layer 3 is cured and the resistor body is obtained, atomic layer deposition and vapor deposition of polymer are no longer performed, and the resistor device covered with the silicone resin layer 3 is directly used as the sample.

[0036] Comparative Example 2: The process is essentially the same as in Example 1, except that the preparation steps of the first barrier layer 4 and the second barrier layer 5 are omitted. After obtaining the resistor body, a secondary encapsulation is performed on the outside of the silicone resin layer 3 using epoxy resin. Specifically, the resistor body is placed in a mold, and a two-component epoxy resin (Epo-tek 301-2) is coated on the surface of the resistor body. It is pre-cured at 65°C for 2 hours, and then fully cured at 100°C for 4 hours to form an epoxy resin outer encapsulation layer with a thickness of approximately 15 micrometers.

[0037] Comparative Example 3: The experiment is essentially the same as in Example 1, except that only the first barrier layer 4 is formed, and the second barrier layer 5 is not prepared. That is, after the atomic layer deposition of an inorganic nanolayer of about 100 nm is completed, it is used directly as a sample, and the surface is not covered with a parylene film.

[0038] Comparative Example 4: The process is essentially the same as in Example 1, except that the first barrier layer 4 is not an inorganic nanolayer, but a single material layer. Specifically, a pure aluminum oxide monolayer film with a total thickness of 100 nanometers is continuously deposited on the silicone resin layer 3 of the resistor body using the same atomic layer deposition process as in Example 1. Then, a 15-micrometer-thick parylene layer is deposited as the second barrier layer 5 using the same method as in Example 1. Everything else is the same as in Example 1.

[0039] Comparative Example 5: The process is essentially the same as in Example 1, except that the first barrier layer 4 is not an inorganic nanolayer, but a single material layer. Specifically, a pure titanium dioxide monolayer film with a total thickness of 100 nanometers is continuously deposited on the silicone resin layer 3 of the resistor body using the same atomic layer deposition process as in Example 1. Then, a 15-micrometer-thick parylene layer is deposited as the second barrier layer 5 using the same method as in Example 1. Everything else is the same as in Example 1.

[0040] Comparative Example 6: It is basically the same as Example 1, except that ozone pulse activation is not performed.

[0041] Performance testing: Ten high-precision resistor samples prepared in the above embodiments and comparative examples were randomly selected from each sample, with a nominal resistance of 1kΩ. High-temperature and high-humidity bias tests were conducted according to JIS C 5201-2 standard: temperature 85±2℃, relative humidity 85±5%, and a rated voltage of 5V DC bias applied to the samples. Resistance was measured using a high-precision digital bridge (measurement accuracy 0.001%) at 25℃ before testing, and at 500, 1000, 2000, and 3000 hours of testing. The resistance change rate (ΔR / R, average absolute value) was calculated. A resistance change rate ≥±5% during the test was considered a failure. Testing of failed samples was stopped, while testing of unfailed samples continued until all samples failed or the power-on time reached 3000 hours, at which point the test ended.

[0042] The test results are shown in Table 1 below: Table 1 (%):

[0043] Note: " / " indicates that the sample has failed (resistance change rate ≥ ±5%) before this time point, and the test is terminated.

[0044] As shown in Table 1 above, the dual-layer composite protective structure of "inorganic nanolayered first barrier layer and vapor-deposited polymer second barrier layer" proposed in this invention can synergistically leverage the dual advantages of nano-interface barrier and polymer hydrophobic buffer. Compared with traditional single-layer silicone resin, silicone / epoxy composite encapsulation, single inorganic thin film, or single polymer layer, the solution of this invention can significantly improve the service life of high-precision resistors in the "double 85" aging test, while keeping the resistance change rate within 0.5%. It solves the problem of precision degradation and failure of thin film resistors caused by electrochemical corrosion under harsh environments, and has outstanding substantive features and significant progress.

[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-precision resistor device, comprising a resistor body, said resistor body being composed of a ceramic substrate; a resistor alloy film layer formed on said ceramic substrate; and a silicone resin layer covering said resistor alloy film layer; characterized in that, It also includes a first barrier layer and a second barrier layer covering the silicone resin layer; the first barrier layer is an inorganic nanolayer stack, which is composed of nanolayers of at least two different metal oxides stacked alternately; the second barrier layer is a vapor-deposited polymer layer formed on the first barrier layer.

2. The high-precision resistor device as described in claim 1, characterized in that, The inorganic nanolayer is composed of alternating layers of aluminum oxide nanolayers and titanium dioxide nanolayers.

3. The high-precision resistor device as described in claim 1, characterized in that, The total thickness of the inorganic nanolayers is 50-200 nanometers.

4. The high-precision resistor device as described in claim 1, characterized in that, The first barrier layer is fabricated using atomic layer deposition (ALD) technology.

5. The high-precision resistor device as described in claim 4, characterized in that, The atomic layer deposition process uses ozone or oxygen plasma as the oxygen source.

6. The high-precision resistor device as described in claim 1, characterized in that, The vapor-deposited polymer layer is parylene.

7. The high-precision resistor device as described in claim 1, characterized in that, The thickness of the vapor-deposited polymer layer is 5-25 micrometers.

8. The high-precision resistor device as described in claim 1, characterized in that, The resistance alloy film is a nickel-chromium alloy or tantalum nitride film, and the resistance alloy film has a resistance pattern, which is formed by photolithography and laser trimming.

9. The high-precision resistor device as described in claim 1, characterized in that, Its preparation methods include: The resistor body is placed in an atomic layer deposition reaction chamber, and at least two kinds of metal precursors and oxygen source precursors are alternately introduced to grow a first barrier layer in situ on the silicone resin layer, which is composed of alternating stacks of different metal oxide nanolayers. A resistor body with the first barrier layer is placed in a vapor deposition system, and a polymer layer is deposited on the first barrier layer to form a second barrier layer.

10. The high-precision resistor device as described in claim 9, characterized in that, The silicone resin layer is ozone activated before the first barrier layer is formed.